Ethno-Edible Mushroom of Pleurotus sp., Clytocybe nebularis and Auricularia auricula in Ranupani Village, East Java - Jehan Ramdani Haryati; Rodiyati Azrianingsih (Journal of Tropical Life Science, 2012)
This paper documented the knowledge about the wild edible fungal flora of Ranupani Village of East Java Indonesia that used by indigenous Tenggerese tribes. Study was conducted by using semi-structured interview and purposive sampling. Data were analyzed quantitatively descriptive. Index of Cultural Significance (ICS) was used to evaluate the importance of non-wood forest yields for local people. Identification of edible mushrooms was based on Guidelines of Flora Diversity Data Collection. This study was focus on the three edible mushrooms which are eaten mostly by the villagers, i.e. Pleurotus sp., Clytocybe nebularis and Auricularia auricula. The result is the Ranupani residents perception of edible mushrooms and its potential as an alternative source of food based on local knowledge and local wisdom of Tenggerese. Pleurotus sp. has the highest preference and intensity to be consumed with 3,2 ICS. It means culturally, this edible mushroom were not too important but intensively used as a secondary food sources such as soup (added or sauted), chips (dried) and fried. Ranupani Villagers always consumed edible mushrooms in rainy season. The ability of residents to distinguish edible mushrooms are equal to the searching ability to find edible mushroom substrate. The residents will recognized the substrate of edible mushrooms on dead trunks of Pasang Tree (Lithocarpus sundaicus), Danglu (Engelhardia spicata), Kemlandingan (Albizia Montana), Casuarina (Casuarina junghuhniana) and acacia (Acacia decurens). Residents who do not have the ability to distinguish and searching were consumer, get the edible mushrooms by buying from the searcher or distributor in packs. The characteristics of an edible mushrooms are a discrete soft flesh of the fruit body, dark color, no ring on the stipe, the presence of insects (e.g. moths) in the lamellae) and the type of mushroom substrate. There were also assisted growths of wild mushrooms by the residents’ raw chop the dead tree trunk as a substrate deliberately. Respondents who knew the time of harvesting edible mushroom were 58.3%. Pasang mushrooms (natural & assisted growth) can be found throughout the rainy season, with an interval of 12 days for subsequent retrieval. While Barat and Kuping mushrooms are found throughout the rainy season, but randomly distributed in the forest. There were unwritten but spoken hereditary local wisdom for the sustainable of the edible mushrooms in Tengger. Only Tenggerese allowed collecting and selling the edible mushrooms in Tengger area to the Tenggerese themselves and tourist (local or foreign). This wisdom is supported by TNBTS regulation that the edible mushroom were not allowed exported out of TNBTS area. This wisdom expectedly makes sure that the edible mushrooms should be sustained in the forest. Keywords:Ethno-edible mushrooms, Ranupani